Quality perception of organically grown tomatoes (Lycopersicon esculentum Mill.) in Vienna, Austria (International Journal of Agricultural Research, Innovation and Technology, 2016)
Austria is one of the major organic tomato producing countries for local and export marketing. These tomatoes are produced in parts of Austria especially around Vienna where their production system has to meet stringent organic quality standards in both local and international markets. These quality standards may put considerable strain on farmers and are normally formulated without famers participation so may not be wholly representative of the farmers quality interpretation. The aim of this paper is therefore to determine the Austrian organic tomatoes growers perception and practice of quality and challenges. Qualitative semi-structured interviews were carried out among 28 organic tomatoes farmers in Vienna, Austria. Findings suggest that quality of organic tomatoes is mainly perceived in terms of both informal values (big fruit size, long shelf life, food security and amount of income received from tomato sales) as well as formal norms (non- application of chemicals, human health, damage free, sweet taste, red colour, and juiciness). There were no gendered differences in quality perception among the growers. High costs of production inputs were identified as the main challenge to attaining quality in organic tomatoes. Following these findings, there is need for effective participation of growers in formulation of standards as well as subsidizing of production inputs by the government. The Austrian tomato growers as well as local and international retailers should work closely to increase the price received by the Austrian organic tomato growers so that it more adequately covers their production costs.Int. J. Agril. Res. Innov. & Tech. 5 (2): 16-20, December, 2015